Calcium Control of the Sign of Phototaxis in Brown Algal Gametes of Mutimo cylindricus. (27th April 2017) - Kinoshita, Nana; Nagasato, Chikako; Motomura, Taizo
Abstract: Brown algal swarmers usually exhibit positive or negative phototaxis. Such behaviors influence the increasing or decreasing dispersal distance or colonization on the new substratum. We confirmed that the sign of phototaxis (negative or positive) in male gametes of Mutimo cylindricus was affected by extracellular Ca 2+ influx through Ca 2+ channels. Under the control condition (10 −2 m [Ca 2+ ]), male gametes swimming with a helical rotation of their cell body mostly showed positive phototaxis. At 10 −3 m [Ca 2+ ], more than half of the male gametes showed positive phototaxis, whereas the others showed negative phototaxis. From 10 −4 –10 −5 m [Ca 2+ ], the phototactic sign changed to negative. When these negative phototactic gametes were transferred back to the control condition, the phototactic sign reverted to positive. At 10 −6 m [Ca 2+ ], some of male gametes showed negative phototaxis, but most showed no phototaxis or flagellar beating. Lanthanum, a Ca 2+ channel blocker, affected the sign of phototaxis at 10 −4 m [La 3+ ] under 10 −2 m [Ca 2+ ], and male gametes mostly showed negative phototaxis. A further increase in [La 3+ ] inhibited phototaxis and flagellar beating. These results pointed out the involvement of Ca 2+ channels that were blocked by La 3+ in phototaxis and flagellar beating. Abstract : Male gametes of the brown alga Mutimo cylindricus typically show positive phototaxis in seawater (10 −2 m [Ca 2+ ]). When the extracellular [Ca 2+ ] decreased to 10 −2 –10 −6 m, male gametes changed the phototactic sign from positive to negative. And this change was reversible, meaning that positive phototaxis was recovered again in 10 −2 m [Ca 2+ ]. Ca 2+ channels that were inhibited by La 3+ also affect their sign of phototaxis. Therefore, it was suggested that the sign of phototaxis of M. cylindricus gametes would be affected by the extracellular Ca 2+ influx through Ca 2+ channels that were blocked by La 3+ .